Research on real-time reliability evaluation method integrated with online fault diagnosis - Liu, Peng (Strojniški vestnik, 2022)
In the dynamic complex subsea environment, the degradation of the ocean engineering system is caused not only by a certain factor but by multiple ones. It is that when the failure rate of a certain component increases significantly, the declining trend in reliability of the entire system is well worth to discussion. This article contributes a real-time reliability evaluation method integrated with online fault diagnosis stage by using dynamic Bayesian networks. The subsea all-electric Christmas tree mechanical system is adopted to demonstrate the proposed methodology, the method realizes the identification of component fault types and the real-time reliability evaluation of the mechanical system under different component failure rates. The problem of inaccurate evaluation results caused by only considering component degradation rate or using sensor data as a single piece of evidence has been overcome. As a supplement to the method, by using mutual information to conduct sensitivity analysis on the reliability of the mechanical system, the importance of the basic events of each component on the reliability of the system is finally given. The proposed method provides important theoretical support for the maintenance of the tree, and can be extended to the reliability evaluation of general subsea production systems.
Keywords: analiza občutljivosti; analiza zanesljivosti; Bayesian network; Bayesovo omrežje; diagnostika napak; električna božična drevesa; fault diagnosis; reliability evaluation; vrednotenje zanesljivosti